2022
DOI: 10.3390/plants11243445
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of Bacillus cereus-Amazcala (B.c-A) with SiO2 Nanoparticles Improves Its Role as a Plant Growth-Promoting Bacteria (PGPB) in Chili Pepper Plants

Abstract: Agriculture needs to decrease the use of agrochemicals due to their high toxicity and adopt new strategies to achieve sustainable food production. Therefore, nanoparticles (NPs) and plant growth-promoting bacteria (PGPB) have been proposed as viable strategies to obtain better crop yields with less environmental impact. Here, we describe the effect of silica nanoparticles (SiO2-NPs) on survival, antioxidant enzymatic activity, phosphate solubilization capacity, and gibberellin production of Bacillus cereus-Ama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 51 publications
0
12
0
1
Order By: Relevance
“…One of the reasons for the enhancement of mineral compounds solubilization in soil may be due to the production of siderophores through metabolites of bacterial [ 34 ]. In addition, a study showed that Bacillus cereus -Amazcala (B.c-A) increased the phosphate solubilization capacity [ 35 ]. Production of phytohormones …”
Section: Plant Beneficial Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the reasons for the enhancement of mineral compounds solubilization in soil may be due to the production of siderophores through metabolites of bacterial [ 34 ]. In addition, a study showed that Bacillus cereus -Amazcala (B.c-A) increased the phosphate solubilization capacity [ 35 ]. Production of phytohormones …”
Section: Plant Beneficial Microorganismsmentioning
confidence: 99%
“…It has been reported that Bacillus subtilis can produce cytokinin and induce an enhancement in root and shoot weight [ 38 ]. In addition, Bacillus amyloliquefaciens produced a high concentration of gibberellic acid [ 35 ]. Inoculation of plants with PGPR increased plant growth.…”
Section: Plant Beneficial Microorganismsmentioning
confidence: 99%
“…Both biostimulation and elicitation are positive plant responses that, based on the hormesis phenomenon, can be defined as part of the eustress zone in the biphasic hormetic curve [ 1 , 17 ]. The case of elicitation is interesting to highlight because if it is excessive, the plant will be in distress, thus showing symptoms of toxicity as suggested above [ 1 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…can synthesize auxin phytohormones (Indole 3-Acetic Acid/IAA) which functions to increase growth, because the dichotomy of chili plants can grow optimally [13]. [14] added plant height can increase thanks to the application of biofertilizer made from Bacillus. 1 shows that the composition of 75% NPK fertilizer + sludge compost is able to provide harvest age relatively the same as the provision of 100% NPK fertilizer.…”
Section: Growth Of Chili Plants Given Various Doses Of Composition Of...mentioning
confidence: 99%